Portability and flexibility of physiotherapy tools for rehabilitation of people with obesity - Abdul Rahman, Julaila; Zabidi, Nur Shahirah Nabilah; Kamaruddin, Zumahiran; Awang, Arita Hanim (Zes Rokman Resources, 2017)
The obesity rate in Malaysia is kept on increasing year by year. The causes for this issue are including unhealthy food intake and unhealthy lifestyle. As the obesity issues in Malaysia worsen, it leads to other problem such as diabetes,heart attack, stroke and also others physical problem. One of it is concerning on physical condition of the ankle. Theankle is the most important parts of a human structure that will affect human body posture. This means that activities were done are heavily influence by ankle condition leads to inefficiency of job performance. Physiotherapy tools are important for the rehabilitation process. The rehabilitation process is known as a healing process, which is essential in ensuring the improvement of health and physical condition of a patient, especially with obesity. Physiotherapist treatment is essential to ensure the effectiveness of rehabilitation process. Therefore, this research aims to understand the portability and flexibility of physiotherapy tools for people with obesity especially in dealing with their job performance. The objective of this study is to identify the physiotherapy tools in the rehabilitation process and to determine the portability and flexibility of the physiotherapy tools for the rehabilitation. Research methods were employed during the process of this study, which includes literature review, product line-up and interviews From this research, portability, and flexibility of the physiotherapy tools for the rehabilitation can help the patient to conduct self rehabat their homes thus boosting their healthy lifestyle. Based on the findings of this study, a new physiotherapy tools need recommended providing an excellent portability and flexibility in terms of the physiotherapy tools for obese patients.